(untitled) (Journal of Atomic and Molecular Sciences, 2018)
SN2 reaction gained much attention because of its vital role in biomolecular and organic chemistry. In the past decades, great progress on mechanism understanding of SN2 reaction has been made by a lot of papers. However, atomic details of the reaction are complicated and hard to explore without precise potential energy surface. In this report, an ab initio molecular dynamics method shed light on the reaction explorations. Although a potential energy surface is disable, we can still make contributions on the mechanism study. Here, we found a novel mechanism in F⁻+CH3Cl→Cl⁻+CH3F that shared common transition state with abstract mechanism but avoid the proton transfer channel. It is a combination of proton roundabout and classical back-side attack mechanism, which is never observed in previous papers. Interestingly, a hydrogen bond transfer process exists in the novel mechanism which simultaneously involved in both C-H-F and Cl-H-F hydrogen bond. It provides another channel of proton transfer in low collision energy, and shows that more explorations have to be carried out even though various mechanism of SN2 reaction have been reported.